Efficiency Comparison of Different Ratio Estimators of Population Variance: A Study on Sugarcane Data (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
This study provides a concise overview of comparison of ratio estimators, specifically focusing on their application in estimating the population variance of a study variable. The estimators use the additional information on a single auxiliary variableto improve the accuracy of the estimation process. The paper presents different ratio type estimators in the literature, arranged chronologically. It discusses the large sampling properties, including biases and mean squared errors, of these estimators for orderone approximation. The manuscript provides mathematical expressions for the bias and mean squared error of each estimator up to the first order of approximation. The estimators are compared both theoretically and empirically and one with highest efficiency is recommended for practical applications.